Petrophysical characterisation of volcanic ejecta to constrain subsurface lithological heterogeneities: implications for edifice stability at basaltic volcanoes - Di Muro, Andrea; Schwarzlmueller, Fabian; Kueppers, Ulrich; Heap, Michael; Dingwell, Donald (Volcanica, 2021)
Piton de la Fournaise (PdF) is a basaltic volcano whose activity is characterized by effusive to mildly explosive eruptions. The geologic record preserves evidence of explosive eruptions associated with the seaward sliding of the steep east flank. Such eruptions formed calderas that are several km in diameter and their products have been emplaced as breccias. The breccias of PdF offer the opportunity to sample a wide range of different lithologies covering most of the stratigraphy of the edifice. Petrophysical measurements revealed a corresponding variability in density, porosity, P-wave velocity, and uniaxial compressive strength, confirming the petrophysical consequences of the lithological diversity. Different lithologies cannot simply be distinguished on the basis of their physical properties. We infer that volcano instability should not be interpreted solely in terms of altered rock units. The large heterogeneity of crustal rocks must be considered when interpreting monitoring data and assessing hazards related to volcano stability.